The use of contact lenses during water-polo play: A 20-year study of Japanese college players - Komori, Y.; Kobayashi, D.; Murase, Y.; Enomoto, I.; Takagi, H.; Kono, I. (Journal of Sports Sciences, 2013)
This study investigated the extent of contact-lens use in Japanese college water-polo male players over 20 years (1991-2011, once every five years). Information about the use of contact lenses during play and the types of contact lens was obtained through a self-report questionnaire.